Molecular Emissions from Circumstellar Envelopes in the Presence of a Binary Companion - Tran, Ngoc Hung; Dinh, Trung Van; Pham, Dong Bang; Nguyen, Thanh Bao Thi (Communications in Physics, 2021)
Following our previous work on the hydrodynamic simulations of the structure of circumstellar envelopes in the presence of a binary companion, in this paper we present the results of radiative transfer calculations for molecular emission line HC3N J=5 – 4 from these simulated circumstellar envelopes. We show that the molecular line emission traces closely the spiral pattern and the associated density enhancement induced by the presence of the binary companion. The molecular emission provides the spatial kinematics of the features within the envelope, which is valuable for estimating the orbital parameters of the binary system and for inferring the physical conditions of the gas within the envelope. We also show that the appearance of the molecular emission depends on the viewing angle resulting in a range of shapes from the spiral pattern to ring-like features, similar to that observed recently in a number of circumstellar envelopes at high angular resolution.